De la banca privada a la gran banca. Antonio Basagoiti en México y España, 1880-1911 - Marichal, Carlos (El Colegio de México, A.C., 1999)
The present essay follows the professional and business career of Antonio  Basagoiti Arteta, one of the most important bankers of the late 19th Century in Mexico. The article analizes his transition from merchant, to merchant banker and finally to leading banker, active in both Mexico and Spain. A typology of this transition from merchant to bankers is attempted with the objective of exploring a key facet of one sector of the Porfirian elite and more particularly  of the role of Spanish entrepreneurs in the Mexican economy of the period.